Correct allometric analysis is always helpful for scaling flow‐mediated dilation in research and individual patient contexts. (8th November 2017) - Lolli, Lorenzo; Batterham, Alan M.; Atkinson, Greg
Summary: McLay et al. (Clin Physiol Funct Imaging (2017); DOI:10.1111/cpf.12465 ) recently examined whether the allometric scaling of flow‐mediated dilation influenced the mean difference between samples of young and older adults compared with the traditional percentage change approach. They also explored whether a new scaling calculation improved the ability to obtain individually scaled flow‐mediated dilation. In our response to their study, we can demonstrate that McLay et al . (Clin Physiol Funct Imaging, 2017) have (i) managed to formulate a new scaling index which does nothing to remove the dependency of that index on baseline diameter and (ii) suggested, incorrectly, that the original allometric approach cannot be used to derive individually‐adjusted values of flow‐mediated dilation, which can be interpreted in a similar way to a percentage change.